The Costs and Consequences of Adequately Managed Chronic Non‐Cancer Pain and Chronic Neuropathic Pain. Issue 1 (6th March 2013) - Andrew, R.; Derry, Sheena; Taylor, Rod S.; Straube, Sebastian; Phillips, Ceri J.
Abstract Background Chronic pain is distressing for patients and a burden on healthcare systems and society. Recent research demonstrates different aspects of the negative impact of chronic pain and the positive impact of successful treatment, making an overview of the costs and consequences of chronic pain appropriate. Objective To examine recent literature on chronic noncancer and neuropathic pain prevalence, impact on quality and quantity of life, societal and healthcare costs, and impact of successful therapy. Methods Systematic reviews (1999 to February 2012) following PRISMA guidelines were conducted to identify studies reporting appropriate outcomes. Results Chronic pain has a weighted average prevalence in adults of 20%; 7% have neuropathic pain, and 7% have severe pain. Chronic pain impeded activities of daily living, work and work efficiency, and reduced quality and quantity of life. Effective pain therapy (pain intensity reduction of at least 50%) resulted in consistent improvements in fatigue, sleep, depression, quality of life, and work. Conclusion Strenuous efforts should be put into obtaining good levels of pain relief for people in chronic pain, including the opportunity for multiple drug switching, using reliable, validated, and relatively easily applied patient‐centered outcomes. Detailed, thoughtful and informed decision analytic policy modeling would help understand the key elements in organizational change or service reengineering to plan the optimum pain management strategy to maximize pain relief and its stream of benefits against budgetary and other constraints. This paper contains the information on which such models can be based.